The Sanctum Abode: Cemetery, Crematorium and Columbarium - Ashoka, Ashoka (Architecture Department, Engineering Faculty, Universitas Diponegoro, 2025)
Semarang City faces challenges in providing burial grounds due to rapid population growth and limited green spaces. To address this issue, The Sanctum Abode was designed as an integrated facility comprising a crematorium, columbarium, and vertical cemetery. The design employs a narrative architectural approach, creating sacred and serene spaces for visitors to reflect, aiding in the healing process of grief. This study combines site analysis, demographic data, and spatial requirements to develop a concept that is efficient, aesthetic, and sustainable. The design not only addresses land scarcity but also enriches urban planning by considering environmental sustainability and the spiritual needs of the community.